Aktivitas secara in vitro dan in vivo kombinasi ekstrak daun kelor (Moringa oleifera lam.) dan pegagan (Centella asiatica (l.). Urb.) sebagai gel anti jerawat - Ninik Setya Hastuti; Shelly Taurhesia; Agung Eru Wibowo (Intisari Sains Medis, 2019)
Background: Acne is a skin problem that is common in everyday life. Expressions of acne can cause psychological problems because of appearance. Moringa leaf extract and herbs contain alkaloid compounds, flavonoids, saponins, tannins and phenolics that can be used as antibacterial, reduce inflammation, reduce sebum glands and moisturize the skin. The purpose of this study was to conduct an in vitro and in vivo analysis of gel activity in combination of Moringa Oleifera L. leaf extract and Centella asiatica (L.). Urb.) Herb or KEKP gel as an anti-acne gel.Method: Activities carried out in vitro with an antibacterial effect on P. acnes, in vivo are carried out by clinical observation and measurement of sebum secretion. The gel contains the same combination of extracts. Twelve volunteers who met the inclusion and exclusion criteria followed the in vivo test to determine the safety and benefits of KEKP gel.Results: At a concentration of 0.78% dilution shows a diameter of 10.4 mm inhibitory power. Medikline as a positive control gives better results compared to KEKP gel with a minimum inhibition diameter of 16.6 mm. Clinical improvement was assessed by reduced signs of inflammation, the number of papules, pustules, nodules and changes in sebum levels measured using a skin analysis tool.Conclusion: The results showed that KEKP antifungal gel invitro had antibacterial activity, and in vivo showed real clinical differences